ADHM polytopes - James P. Allen; Paul Sutcliffe (Journal of High Energy Physics, 2013)
Spinal cord injury (SCI) remains a major clinical challenge because the inflammatory and oxidative microenvironment drives secondary tissue damage. Although mollugin (Mol) possesses anti-inflammatory, antioxidant, and neuroprotective activities, its therapeutic application is limited by poor water solubility and rapid clearance. In this study, we developed a RVG-modified liposomal nanoplatform for targeted delivery of mollugin (Mol@Lip-RVG) as a novel therapeutic strategy for SCI. The Mol@Lip-RVG nanoplatform exhibited excellent biocompatibility, favorable physicochemical characteristics, and sustained drug release profile. In vitro studies demonstrated that Mol@Lip-RVG effectively downregulated pro-inflammatory mediators, promoted microglial polarization from the pro-inflammatory M1 phenotype toward the anti-inflammatory M2 phenotype, and significantly reduced reactive oxygen species production. In SCI mice, the RVG modification enabled efficient crossing of the BSCB and selective accumulation at the injury site through specific binding to nAChRs. This targeted delivery resulted in enhanced neuro-preservation and substantial improvement in motor function recovery, achieved through dual modulation of microglial reprogramming and attenuation of oxidative stress. Mechanistically, we demonstrated that Mol@Lip-RVG exerts its therapeutic effects is associated with inhibition of the NF-κB signaling pathway, thereby suppressing neuroinflammation. Collectively, these findings establish the Mol@Lip-RVG nanoplatform as a promising targeted therapeutic approach that addresses both the delivery challenges and complex pathophysiology of spinal cord injury.